Cinema of Wisdom: The use of film media to promote morality, ethics and reduce cyberbullying in youth - Sukbunjhong, Sammiti (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The objectives of this research are 1) to experiment with using films as a medium to create recognition in reducing cyberbullying behavior of youth through online social media, 2) to study to effect of using academic film media to promote morality and ethics, and create recognition in reducing cyberbullying behavior of youth in school. This study employed mixed method research by collecting quantitative data to obtain the overview of the study. Then the samples were screened for the qualitative research through in-depth study of the data. The population of this study was 53 primary-level students from Wat Adisorn School, ranging from Prathom 2 to 6. Screening the sample population for the qualitative research resulted in a group of 15 students for the study. The quantitative data indicated that out of 53 students 64.2% were male; 22.6% each were in Prathom 3 and 4; 58.5% lived with their parents; 79.2% of the parents were employees; 100% used or knew of at least one social media platform; 98.1% used social media through mobile phones; and 43.4% spend less than one hour on social media in one day; and 100% realized that bullying was bad. Furthermore, when one focused on those having no recognition of cyberbullying through social media, one discovered that 13.2% did not recognize cyberbullying through social media with higher percentage of male than female (57.1% vs. 42.9%); 42.9% each studied in Prathom 3 and 5; 71.4% lived with their parents; 85.7% of the parents were employees; 100% used or knew of at least one social media platform; 100% used social media through mobile phones; and 42.9% each spend less than one hour or more than six hours on social media in one day; 100% realized that physical bullying was bad; and 100% realized that cyberbullying through social media was bad. After viewing the film media, the sample group gained better understanding about cyberbullying through social media and were able to explain the content of the film showing that cyberbullying was bad. They also empathized with the ones being bullied as well as the bullies on the impact in various aspects. Moreover, the sample group did not want to be either the one being bullied or the bully, bringing about the intention to reduce their cyberbullying behaviors eventually.